Non-Price Competitiveness of Exports from Emerging Countries - Konstantins Benkovskis; Julia Wörz (FIW - Research Centre International Economics, 2012)
We analyse EMEs global competitiveness whereby we explicitly take account of non-price aspects of competitiveness building on the methodology developed in Feenstra (1994) and Broda and Weinstein (2006) and the extension provided in Benkovskis and Wörz (2012). We construct an export price index which adjusts for changes in the set of competitors (variety) and changes in non-price factors (quality in a broad sense) for a set of nine large emerging economies (Argentina, Brazil, Chile, China, India, Indonesia, Mexico, Russia and Turkey). We use a highly disaggregated data set at the detailed 6-digit HS level over the period 1999-2010. In contrast to the conclusions based on the CPI-based real effective exchange rate we find that there are rather pronounced differences between individual markets. As a first and important result, China shows a huge gain in international competitiveness due to non-price factors thus suggesting that the role of Renminbi undervaluation for China's competitive position may be overstressed. The strong improvements in Russia's non-price competitiveness are exclusively due to developments in the oil sector as are the competitive losses observed for Argentina and Indonesia. Further, Brazil, Chile, India, and Turkey show discernible improvements in their competitive position when accounting for non-price factors while Mexico's competitiveness has deteriorated regardless of the index chosen.
Keywords: C43; F12; F14; L15; 330; non-price competitiveness; quality; relative export price; emerging countries